2004
DOI: 10.1037/h0100127
|View full text |Cite
|
Sign up to set email alerts
|

FAP-enhanced group therapy for chronic pain.

Abstract: There is a firm tradition of cognitive behavioral programs for chronic pain and structured treatments for training coping skills have been relatively successful with motivated and cooperative participants. However, what is being trained generally comes down to component skills and ways of thinking that have to be used by the client in complex real life situations. The aim of this paper is to illustrate how the principles of Functional Analytic Psychotherapy (FAP) can be applied in a group therapy program for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
0
13
0
2
Order By: Relevance
“…Functional Analytic Psychotherapy (FAP) , with its behavioral focus on in vivo interactions and in-session equivalents of clients' daily life problems, offers a compelling conceptual framework from which to conduct interpersonal group psychotherapy Vandenberghe, Ferro, & Furtado da Cruz, 2003). Although a wide variety of cognitive behavioral and behavioral approaches have been applied to group psychotherapy for issues such as skills training, coping deficits, and changes in thinking (Fisher, Masia-Warner, & Klein, 2004;James, Thorn, & Williams, 1993;Rittner & Smyth, 2000;Rhode, Jorgensen, Seeley, & Mace, 2004;Wilson, Bouffard, & Mackenzie, 2005), behaviorally oriented groups are generally characterized by the use of behavior modification techniques (Vinagrov, Co, & Yalom, 2003) and do not focus on interpersonal process.…”
Section: Renee Hoekstra and Mavis Tsaimentioning
confidence: 99%
See 1 more Smart Citation
“…Functional Analytic Psychotherapy (FAP) , with its behavioral focus on in vivo interactions and in-session equivalents of clients' daily life problems, offers a compelling conceptual framework from which to conduct interpersonal group psychotherapy Vandenberghe, Ferro, & Furtado da Cruz, 2003). Although a wide variety of cognitive behavioral and behavioral approaches have been applied to group psychotherapy for issues such as skills training, coping deficits, and changes in thinking (Fisher, Masia-Warner, & Klein, 2004;James, Thorn, & Williams, 1993;Rittner & Smyth, 2000;Rhode, Jorgensen, Seeley, & Mace, 2004;Wilson, Bouffard, & Mackenzie, 2005), behaviorally oriented groups are generally characterized by the use of behavior modification techniques (Vinagrov, Co, & Yalom, 2003) and do not focus on interpersonal process.…”
Section: Renee Hoekstra and Mavis Tsaimentioning
confidence: 99%
“…As current publications in support of FAP application to groups (Hoekstra, 2008;Vandenberghe et al, 2003) are theoretical in nature, future directions for FAP groups could include empirical data collection. The FAP Session Bridging Form and the FAP Experience of Closeness in the Therapeutic Relationship could easily be modified to collect information about groups between sessions.…”
Section: Future Directions and Precautionsmentioning
confidence: 99%
“…Recently, a small randomized trial comparing FAP to a brief, supportive condition with a transdiagnostic college‐counseling patient sample found significant improvements in interpersonal functioning and significant decreases in overall psychiatric symptom severity for FAP compared with the supportive control (Maitland et al ., ). While the majority of studies have been conducted in the United States, a small number of studies found evidence that FAP benefitted clients from other countries, such as Brazil (Vandenberghe et al ., ), Spain (Esparza et al ., ) and Columbia (Ferro et al , 2006).…”
mentioning
confidence: 99%
“…Findings are accumulating in support of the efficacy of FAP. Clinical case studies suggested that FAP is effective in improving ideographically defined interpersonal problems for patients with histrionic and narcissistic personality disorders (Callaghan, Summers, & Weidman, 2003), chronic pain (Vandenberghe, Ferro, & Furtado da Cruz, 2003), obsessive compulsive disorder (Kohlenberg & Vandenberghe, 2007) and depression (García, Aguayo, & Montero, 2006). Controlled single-subject designs with multiple patients have demonstrated that FAP improves patientsˈ problems when added to baseline conditions consisting of CBT (Kanter et al, 2006), non-specific supportive therapy (Landes, Kanter, Weeks, & Busch, 2013) and behavior analytic therapy (Esparza, Muñoz-Martínez, Santos, & Kanter, 2015;Oshiro, Kanter, & Meyer, 2012).…”
mentioning
confidence: 99%
“…A Psicoterapia Analítica Funcional (FAP) é uma das formas de terapia surgidas nesse período e que se debruçou em uma releitura da relação terapêutica em uma perspectiva analítico-comportamental . Este modelo de terapia se configura como sendo teórico e conceitualmente sólido e demonstra-se bastante útil no processo clínico, como apontam diversas publicações (Follette, Naugle & Callaghan, 1996;Vandenberghe, 2003Vandenberghe, , 2007.…”
Section: Lista De Figurasunclassified